Research on the Reform of English Translation Course Instruction amidst the Prevailing Trend of Machine Translation - Jin, Bingbing; Hu, Mengting (Journal of Educational Research and Policies, 2024)
In recent years, machine translation technology has surged forward at an astounding pace, permeating numerous sectors and dramatically elevating both the efficiency and accessibility of translation services. Nevertheless, this technological advancement presents unprecedented challenges to conventional English translation pedagogy. Given the growing ubiquity of machine translation, a critical question arises: How can we refine and enhance the content and methodologies of translation courses to bolster students' translation competencies, especially their translation quality and adaptability when leveraging machine translation tools? This has become an urgent issue within the realm of translation education. Against this backdrop, this article endeavors to investigate novel approaches to reforming English translation course instruction. The objective is to nurture translation professionals who excel not only in language skills but also in the application of technology, thereby fulfilling the heightened expectations for translation work in the future society.